ANTIBACTERIAL ACTIVITY OF BENTHIC MARINE ALGAE EXTRACTS FROM THE MEDITERRANEAN COAST OF MOROCCO - Zbakh, Hanaƒ¢; Chiheb, Houda; Bouziane, Hassan; Motilva Sánchez, Virginia; Riadi, Hassane (Journal of microbiology, biotechnology and food sciences, 2012)
Marine organisms are potentially prolific sources of highly bioactive secondary metabolites that might represent useful leads in the development of new pharmaceutical agents. The Moroccan marine biodiversity including macroalgae remains partially unexplored in term of their potential bioactivities. Antibacterial activity of methanolic extracts from 20 species of macroalgae (9 Chlorophyta, 3 Phaeophyta and 8 Rhodophyta) collected from Moroccan Mediterranean coasts was evaluated against Escherichia coli, Staphylococcus aureus and Enterococcus faecalis. The extracts of the studied Rhodophyceae inhibited considerably the growth of the three tested bacterial strains and gave inhibition zones between 20 and 24 mm. The results indicate that these species of seaweed present a significant capacity of antibacterial activities, which makes them interesting for screening for natural products.